2021
DOI: 10.3390/ijms22126202
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Metagenomics and Metatranscriptomics to Reveal Microbiomes in Overwintering Pepper Fruits

Abstract: Red pepper (Capsicum annuum, L.), is one of the most important spice plants in Korea. Overwintering pepper fruits are a reservoir of various microbial pepper diseases. Here, we conducted metagenomics (DNA sequencing) and metatranscriptomics (RNA sequencing) using samples collected from three different fields. We compared two different library types and three different analytical methods for the identification of microbiomes in overwintering pepper fruits. Our results demonstrated that DNA sequencing might be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
1
7
0
Order By: Relevance
“…The prevalence of Gammaproteobacteria, particularly the order Enterobacteriales, the family Erwiniaceae , and the genus Pantoea , is conspicuous within the high abundance found in round tomato. Despite its versatility, Pantoea is known to manifest as either a commensal or a pathogenic organism [ 61 ], with reports of its isolation from plants and soil, as well as instances of infecting pepper fruits [ 62 ]. Hence, the notable presence of Pantoea in high abundance on days 6 and 12 in round tomato could potentially suggest a pathogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Gammaproteobacteria, particularly the order Enterobacteriales, the family Erwiniaceae , and the genus Pantoea , is conspicuous within the high abundance found in round tomato. Despite its versatility, Pantoea is known to manifest as either a commensal or a pathogenic organism [ 61 ], with reports of its isolation from plants and soil, as well as instances of infecting pepper fruits [ 62 ]. Hence, the notable presence of Pantoea in high abundance on days 6 and 12 in round tomato could potentially suggest a pathogenic role.…”
Section: Discussionmentioning
confidence: 99%
“…Although methods and bioinformatics tools have been developed for exploring microbiomes in fruits, a suitable strategy should be selected for the aims of study. Previously, Jo et al compared DNA and mRNA libraries and three analytical methods for microbial diversity in overwintering pepper fruits and demonstrated that library types, analytical methods, and proper databases contribute to the achievement of microbiome study [113].…”
Section: Metagenomics In the Food Industrymentioning
confidence: 99%
“…Jo Y et al compared two distinct library types (DNA for metagenomics, RNA for metatranscriptomics) and three different analytical methods for the identification of microbiome in overwintering pepper fruits. Their results revealed that DNA sequencing is more useful for the identification of bacteria and DNA viruses, whereas mRNA sequencing is superior for identifying fungi and RNA viruses [ 15 ].…”
Section: Microbiomicsmentioning
confidence: 99%
“…This Special Issue of the International Journal of Molecular Sciences entitled “Genomics: Infectious Disease and Host –Pathogen Interaction” contains twelve original articles and three reviews that provide new insights into infectious diseases with regard to biofilm formation [ 1 , 2 , 3 ], diagnostics [ 4 ], vaccine development [ 5 ], and host–pathogen interaction [ 6 , 7 ]; these insights are based on genomic [ 8 , 9 , 10 , 11 , 12 ], transcriptomic [ 13 , 14 ], and microbiomic [ 15 ] studies.…”
Section: Introductionmentioning
confidence: 99%